Repetition as a Narrative Tool in Jane Austen’s Pride and Prejudice: Stylistic and Thematic Functions - Seriah,Zadjia Insaf; Naoumi, Mohammed (Faculty of Letters and Foreign Languages Department of English, 2025)
The dissertation explores the use of repetition in Pride and Prejudice as literary and thematic elements, and how repetition contributes to the development of narrative structure and the coherence of themes (such as pride, prejudice, marriage, class). Uses stylistic and descriptive, which allow for a detailed analysis of the novel guide the reader toward a deeper understanding of characters and social values criticized by Jane Austen in her work. Emphasize its particular relevance to Algerian readers by comparing social themes to local context. The results indicate that the repetition was not merely coincidental, but rather aimed to emphasize ideas, reveal character traits, and create coherence throughout the novel